2018
DOI: 10.15557/jou.2018.0004
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Doppler parameters at 36–42 weeks’ gestation in the prediction of adverse perinatal outcomes in appropriate-for-gestational-age fetuses

Abstract: AimTo investigate the potential value of Doppler ultrasound and to assess cerebroplacental ratio (CPR) in the prediction of adverse perinatal outcome defined as Apgar score < 7 at 1 minute.Material and methodsThis was a retrospective cross-sectional study in selected pregnant women undergoing an ultrasound examination between 36 and 42 weeks of gestation. We measured estimated fetal weight (EFW), mean umbilical artery pulsatility index (UA PI), mean middle cerebral artery pulsatility index (MCA PI), CPR, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Regarding ROC analysis, CPRMOM was considered a good negative indicator than a positive one in both cases of CS due to fetal distress at cut-off value 0.97 with sensitivity of 72.7% and specificity 91.4% with AUC 0.778 and P value = 0.005, and in cases of NICU admission at cut-off value 0.84 with sensitivity of 75.0% and specificity 92.3% with AUC 0.827 and P value < 0.001. While CPR was considered a poor indicator for cases of initial Pathological CTG, lower APGAR score and umbilical PH [table 6, figure 3,4,5,6,7]. Our result coincides with Prior et al [27] who reported that abnormal CPR was a better predictor for emergency CS than abnormal UA or MCA.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding ROC analysis, CPRMOM was considered a good negative indicator than a positive one in both cases of CS due to fetal distress at cut-off value 0.97 with sensitivity of 72.7% and specificity 91.4% with AUC 0.778 and P value = 0.005, and in cases of NICU admission at cut-off value 0.84 with sensitivity of 75.0% and specificity 92.3% with AUC 0.827 and P value < 0.001. While CPR was considered a poor indicator for cases of initial Pathological CTG, lower APGAR score and umbilical PH [table 6, figure 3,4,5,6,7]. Our result coincides with Prior et al [27] who reported that abnormal CPR was a better predictor for emergency CS than abnormal UA or MCA.…”
Section: Discussionsupporting
confidence: 88%
“…So, the available screening policy depends on history of disease and intrapartum events do not define high risk cases that prone to intrapartum hypoxia. Therefore, perinatal care should determine the fetuses with hypoxia rather than small fetuses [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increasing number of studies investigate the association of CPR with adverse outcome in low-risk and/or AGA pregnancies [56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Initially, it may appear unconventional to associate CPR with adverse outcome in apparently healthy pregnancies.…”
Section: Association Of Cpr With Adverse Outcomes In Aga Fetusesmentioning
confidence: 99%